(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an in-depth exploration of American English pronunciation standards, tracing their historical development, key phonetic features, regional variations, and implications for English learners. The piece begins by discussing the origins of American English, highlighting the influence of early colonial settlers and the significant role of Noah Webster in standardizing the language. It then details distinct phonetic characteristics, such as rhoticity, vowel pronunciation, and stress patterns, which differentiate American English from other dialects, particularly British English. The article also emphasizes the diversity of regional accents within the United States, illustrating how factors like geography and cultural influences contribute to the unique sound of American English across different areas. Additionally, the implications for English learners are addressed, underscoring the importance of mastering pronunciation for effective communication and cultural understanding. Overall, the article serves as a comprehensive resource for understanding the significance of American-based pronunciation standards in both historical and contemporary contexts, making it valuable for linguists, educators, and learners of English.